Влияние аварийных разливов нефтепродуктов в Керченском проливе на большого баклана - Савицкий, Р.М. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
About 2000 tons of black oil and diesel oil, 6800 tons of sulphur entered sea in the Kerch Strait after tankers' wreck in November 2007. Ornithological investigations have been carried out from 13.11.2007 to 25.02.2008 at Taman Penincula to study the influence on birds of this accident at sea and estimate the damage. Species composition and numbers of dead birds were determined as well as the reasons of their death. The total number of dead birds in the waters of Kerch Strait after the accident at sea was about 12000 individuals. Proportion of the Cormorants among dead birds was 18%.